Analisa Strategi Bisnis pada PT. Unilever Indonesia - Destiana Safitri; Yuliana Shintia; Putri Tazkia; Xena Amanda; Tata Fransiska Putri; Sevilla Nadia Amada; Rizqy Anantia (Jurnal Publikasi Ilmu Manajemen, 2023)
This article aims to analyze the business strategy of PT Unilever Indonesia. PT Unilever Indonesia is a multinational company engaged in the largest staple food in the world. The analysis is carried out in the form of internal, external, and competitive analysis that has been carried out by the company. The results of the analysis show that the company’s strategy is a means of using its strengths to overcome its internal weaknesses. PT Unilever has rapid and significant growth, large market potential, large consumer market demand, innovation and strategy that continues to develop and has government support that is able to fight competitors.